Management of Pratylenchus penetrans and Verticilllium symptoms in strawberry - Bélair, Guy; Coulombe, Jean; Dauphinais, Nathalie (Phytoprotection, 2018)
Under field conditions, the effect of a single rotation with corn, cruciferous crops (canola followed by white mustard) as green manure, oats, and forage pearl millet was measured on the density of Pratylenchus penetrans and its impact on damage and losses caused by Verticillium dahliae in a strawberry plantation the following year. The lowest density of P. penetrans was recorded following forage pearl millet and green cruciferous manure, and in both cases, it was below the known pest threshold in strawberry of 500 P. penetrans kg-1 soil. Both green manure of cruciferous plants and forage pearl millet reduced the incidence of Verticillium wilt and increased the growth of strawberry plants. In the fall, the number of crowns and the number of daughter plants were significantly higher following forage pearl millet or cruciferous plants than corn. The highest wilt symptoms and the lowest strawberry growth were observed in plots previously planted with corn, which also harboured the highest spring populations of P. penetrans. Those results support a positive interaction between P. penetrans and V. dahliae, even more importantly so on susceptible cultivard such as ‘Jewell’.